Corrosion behavior of pyrocarbon coatings exposed to Al2O3–SiO2 gels containing ammonium nitrate. (May 2015) - Wang, Yi; Liu, Haitao; Cheng, Haifeng; Zu, Mei; Wang, Jun
Highlights: The decomposition of ammonium nitrate in Al2 O3 –SiO2 gels was investigated. The corrosion kinetics and behavior of CVD pyrocarbon coatings by AN were studied. Original dense coatings were corroded into porous structure in N440/AS composites. The composite strength was improved remarkably by the coatings. Abstract: The corrosion behavior of pyrocarbon (PyC) coatings exposed to Al2 O3 –SiO2 gels containing ammonium nitrate (AN) was investigated. The formation of nitrogen oxides during the decomposition of AN could enable the oxidation of PyC at relatively low temperature. After corrosion by the gels, severe attack was observed and the surface roughness of the coatings increased remarkably. The degree of crystallization decreased while that of disorder increased in PyC. Finally, PyC coatings were introduced into three-dimensional all-oxide fiber-reinforced composites. We found that the resulting porous coatings were favorable to the fiber/matrix debonding, thereby contributing to the performance improvement.